Pesantren as the Source of Peace Education - Jeanne Francoise (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
This paper gives a new perspective about pesantren (Islamic boarding school) as the source of peace education in Indonesia using three concepts; First is a collective opinion that reflected in the UN Declaration of Culture of Peace, second is the definition of peace education based on peace and conflict resolution studies, and third is the historical side of Islam in Indonesia. To explain the main idea about pesantren as the source of peace education, this paper uses the qualitative method in analyzing the data from interviews in some pesantren in Madura Island in 2014. This paper constructs a hypothesis that pesantren is the unique source and very potential for creating Indonesian peace leaders in the future. This idea is simply coming from a common sense that Muslims majority in Indonesia send their children to the pesantren to have a good education and good manner as well. But on the other side, some pesantren precisely create some radicals, so I would like to uphold this issue by telling the Union European historical experience to handle radicalizes through peace education by harmonizing state-religion relationship.